(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the cytotoxic effects of carbamide peroxide (CP) and hydrogen peroxide (HP) bleaching agents, and their manifestations on teeth. Methods: A literature review was performed on the Pubmed database, using the following descriptors: tooth whitening, cytotoxicity, hydrogen peroxide, carbamide peroxide and pulpal reaction. 29 articles were selected. Review: The most commonly used tooth whitening gels are CP and HP, which achieve the same results at different application times. The inappropriate use of bleaching agents may cause adverse effects, such as cytotoxicity in the pulp tissue, causing from an inflammatory reaction to pulp necrosis, where dental sensitivity was the most common manifestation. HP in higher concentrations is indicated for office techniques, and implies a greater possibility of cytotoxic effect on the pulp tissue, especially if associated with the use of light source, and should also consider the thickness of the dentin in the dental element. Conclusion: Among the different bleaching agents, the use of CP (10%) in home bleaching will result in less cytotoxic effects on teeth, with effective bleaching action, and HP (17.5%) in office bleaching is less cytotoxic when compared to the conventional HP method (35%).